Turbulent Waters : Pursuing Water Security in Fragile Contexts - Sadoff, Claudia W. (World Bank, Washington, DC, 2017)
Water insecurity—ranging from chronic water scarcity to lack of access to safe drinking water and sanitation services, to hydrological uncertainty and extremes (floods and droughts)—can cause severe disruptions and compound fragilities in social, economic, and environmental systems. Untangling the role of water insecurity in contributing to fragility is difficult, yet it is becoming a fundamental question for water policy worldwide given the scale of the fragility challenge. This report explores the dynamics between water insecurity and fragility. It suggests that water security is more difficult to achieve in fragile contexts because of a range of factors, including weak institutions and information systems, strained human and financial resources, and degraded infrastructure. This report focuses on three main mechanisms by which water insecurity and fragility interact: (1) failure to provide citizens with basic water services; (2) failure to protect citizens from water-related disasters; and (3) failure to preserve surface, ground and transboundary water resources.